Histopathological Study of Pathological Specimens of Various Organs in a Tertiary Care Hospital in Bangladesh (TAJ: Journal of Teachers Association, 2021)
This retrospective study of histopathological specimens was done at the Department of Pathology of Rajshahi Medical College, Bangladesh, from July 2019 to June 2020, emphasizing challenges and diagnosis outcomes. Data obtained from their case notes included age at admission, the site from where the specimens were collected, and histopathological diagnosis.  Out of the 2026 histopathology samples, chronic cervicitis constitutes about 50% of the cases. Serous cystadenoma (about 1/4th cases) was common among ovarian pathology. 54.16% of the breast pathology exhibited Invasive ductal carcinoma. Reactive follicular hyperplasia and lymphoma constitute 49.44% of the lymph node pathology. About 80% of the gall bladder pathology was chronic cholecystitis, and metastatic adenocarcinoma was the commonest pathology involving the liver. Squamous cell carcinoma constitutes about 40% of the skin pathology. Osteosarcoma, osteochondroma, and giant cell tumor were the common pathologies involved in bones. Transitional cell carcinoma constitutes about 45% of urinary bladder pathology, and renal cell carcinomas were the commonest pathology of the kidney. Adenocarcinoma constitutes about 45 % of stomach pathology, 28% of small intestine pathology, and 14% of large intestine pathology.  Histopathological specimens at the pathology Rajshahi Medical College department with a wide range of pathologies are a major problem. From this study necessity of screening programs for early cancer detection appeared as a time-demanding issue.TAJ 2021; 34: No-1: 16-25